Ocular pharmacological and biochemical profiles of 6-thioguanine: a drug repurposing study - Trotta, Maria Consiglia; Gesualdo, Carlo; Lepre, Caterina Claudia; Russo, Marina; Ferraraccio, Franca; Panarese, Iacopo; Marano, Ernesto; Grieco, Paolo; Petrillo, Francesco; Hermenean, Anca; Simonelli, Francesca; D’Amico, Michele; et al. (Frontiers in Pharmacology, 2024)
The purine-analogue 6-thioguanine (6TG), an old drug approved in the sixties to treat acute myeloid leukemia, was tested in diabetic retinopathy experimental in vivo setting along with a molecular modeling approach.Methods: A computational analysis was performed to investigate the interaction of 6TG with MC1R and MC5R. This was confirmed in Human Umbilical Vein Endothelial Cells (HUVECs) exposed to high glucose (25mM) for 24h. Cell viability in HUVECs exposed to high glucose and treated with 6TG (0.05-0.5-5 µM) was performed. To assess tube formation, the HUVECs were treated for 24h with 6TG 5 µM and AGRP (0.5-1-5 µM) or PG20N (0.5-1-5-10 µM), MC1R and MC5R antagonists, respectively. For the in vivo DR setting, diabetes was induced in C57BL/6J mice through a single streptozotocin injection. After 2, 6 and 10 weeks diabetic and control mice received 6TG intravitreally (0.5-1-2.5 mg/kg) alone or in combination with AGRP or PG20N. Fluorescein angiography (FA) was performed after 4 and 14 weeks from diabetes. After 14 weeks, mice were euthanized and immunohistochemical analysis was performed to assess retinal levels of CD34, a marker of endothelial progenitor cells formation during neo-angiogenesis. Results: The computational analysis evidenced a more stable binding of 6TG binding at MC5R compared to MC1R. This was confirmed by tube formation assay in HUVECs exposed to high glucose. Indeed, the anti-angiogenic activity of 6TG was abolished by a higher dose of MC5R antagonist PG20N (10 µM) compared to MC1R antagonist AGRP (5 µM). The retinal antiangiogenic effect of 6TG was evident also in diabetic mice, showing a reduction of retinal vascular alterations by FA analysis. This effect was not observed in diabetic mice receiving 6TG in combination with AGRP or PG20N. Accordingly, retinal CD34 staining was reduced in diabetic mice treated with 6TG. Conversely, it was not decreased in diabetic mice receiving 6TG combined with AGRP or PG20N.6TG evidenced a marked anti-angiogenic activity in HUVECs exposed to high glucose and in diabetic retinopathy mice. This seems to be mediated by MC1R and MC5R retinal receptors.